Morphological and Biochemical Characteristics on Different Accession of Pegaga - Tan, Suat Hian (Informatics Publishing Limited, 2017)
Objectives: To examine morphological and biochemical characteristics of commonly available accessions of Centellaasiatica in Malaysia. Methods/Statistical Analysis: Four accessions of Pegaga designated as UPM01, UPM02, UPM03 and UPM04 were collected throughout Malaysia and their morphological characteristics and biochemical contents were investigated. Flavonoid profiling was carried out using High Performance Liquid Chromatography (HPLC). Findings: Accession UPM02 had highest total soluble glucose content with 75.4 mg/g, where lowest in UPM03 39.1 mg/g. Among the four accessions, β-carotene content ranged from 2.11 mg/g to 3.3 mg/g. For flavonoid content, UPM03 had the highest concentration of 8.99 mg/g. The flavonoids present in UPM03 were quercetin, kaempherol, luteolin and rutin while others only had rutin or/and kaempherol. Application/Improvements: The results from the present studies could be a valuable information not only for researchers but also the farmers across the country.